Latihan Range of Motion Aktif Ekstremitas Bawah Meningkatkan Sensitivitas Kaki pada Penyandang Diabetes Mellitus Tipe II: Active Range of Motion Exercises for the Lower Extremities Improve Foot Sensitivity in People with Type II Diabetes Mellitus - Elfrida Apriliani; Sapta Rahayu Noamperani; Nurun Laasara; Abdul Majid (Journal of Health, 2026)
Background: Type II diabetes mellitus is a metabolic disorder caused by impaired insulin secretion and function, the prevalence of which continues to increase. Indonesia ranks 7th in the world with a prevalence of type II diabetes in the Special Region of Yogyakarta of 3.6%. Diabetic neuropathy is a common complication in people with type II diabetes, especially in individuals with suboptimal self-management and can cause decreased foot sensitivity. Objective: This study aims to determine the effect of providing active range of motion of the lower extremities in people with type II diabetes at the Sewon I Community Health Center. Methods: Quantitative research with a Quasi Experimental design and pretest-posttest design with a control group design. Samples were taken using a purposive sampling technique of 60 respondents divided into 30 respondents in the intervention group and 30 respondents in the control group. Results: In the intervention group, 22 respondents (73.3%) experienced improvement to normal and in the control group, 30 respondents (100%) did not experience improvement or still experienced decreased foot sensitivity. The Mann Whitney test showed that there was an effect of active range of motion training of the lower extremities on foot sensitivity with a p value of 0.000. Conclusion: Active lower extremity range of motion exercises can improve foot sensitivity in people with type II diabetes. These findings can form the basis for implementing active ROM exercises as part of education and nursing care to prevent complications of diabetic neuropathy.